A Rare Case of Disseminated Peritoneal Leiomyomatosis: A Case Report - Chirayath, Michael; Titus, Twinkle T.; Sebastian, Loana Mariyam; Cicilet, Soumya (Indian Journal of Radiology and Imaging, 2024)
Disseminated peritoneal leiomyomatosis is a benign condition characterized by multiple extrauterine leiomyomas in various locations such as the peritoneum, mesentery, abdominal wall, and pelvis. This is typically observed following laparoscopic myomectomy and is an extremely rare disease, with only a limited number of cases reported thus far. It primarily affects women in their reproductive age group and is believed to be associated with ovarian secretions. Leiomyomas are monoclonal smooth muscle tumors with characteristics similar to muscle on computed tomography/magnetic resonance imaging. The presence of multiple nodules dispersed throughout the peritoneal cavity may resemble malignancy. There is no conventional treatment guideline, and the approach depends on the patient's age, symptoms, fertility requirements, and previous treatment. The treatment modalities can be surgical, hormonal, or combined. The presented case involves a 40-year-old woman who developed disseminated peritoneal leiomyomatosis after undergoing laparoscopic myomectomy.
Keywords: fibroid; leiomyomas; leiomyomatosis